Effectiveness Of Quantum Learning Model On The Mastery Of Arabic Vocabulary - Akib, Ridha Nurul Fitri; Bachtiar, Fauziah; Hasmawati, Hasmawati (Phonologie : Journal of Language and Literature, 2025)
Abstract. This study is an experimental research that aims to determine the effectiveness of the Quantum Learning model on students' mastery of Arabic vocabulary. The population in this study is grade VIII students of MTs Negeri Ma'rang Pangkep, academic year 2023/2024. In this study, the sample selection used random sampling technique, with a sample of 42 people, consisting of 20 students of class VIII H as the experimental class and 22 students of class VIII I as the control class. The results of the data hypothesis test using the t-test formula show that, t_h (3,271)> t_t (2,021) at a significance level of 0.05 and df = 40. It can be concluded that the Quantum Learning model is effective on the mastery of Arabic vocabulary of grade VIII students of MTs Negeri Ma'rang PangkepKeyword: Quantum Learnig, Arabic, vocabulary